2001
DOI: 10.1007/bf03016832
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular contractility is reduced by hypercapnic acidosis and thoracolumbar epidural anesthesia in rabbits

Abstract: Purpose: We have previously observed that sympathetic blockade by epidural anesthesia (EA) modifies the cardiovascular response to marked hypercapnic acidosis in dogs. Our objective was to determine whether the combination of marked hypercapnic acidosis and EA reduce left ventricular contractility.Methods: We randomly assigned 22 Japanese white rabbits anesthetized with isoflurane (1.0%) to two groups according to the absence (control group, n=11) or presence (EA group, n=11) of thoracolumbar EA. After epidura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…35 58 This concept was supported by the observation in rabbits that although hypercapnoeic acidosis caused a 16% decrease in contractility, a thoracolumbar epidural increased this depression considerably by blocking sympathetic activity. 68 The depression of myocardial contractility produced by respiratory acidosis is also significantly increased after beta-blockade implying a systemic catecholamine effect. 102 In the pulmonary vasculature, however, acidosis increases the response to norepinephrine.…”
Section: Acidosis and Inotropesmentioning
confidence: 99%
“…35 58 This concept was supported by the observation in rabbits that although hypercapnoeic acidosis caused a 16% decrease in contractility, a thoracolumbar epidural increased this depression considerably by blocking sympathetic activity. 68 The depression of myocardial contractility produced by respiratory acidosis is also significantly increased after beta-blockade implying a systemic catecholamine effect. 102 In the pulmonary vasculature, however, acidosis increases the response to norepinephrine.…”
Section: Acidosis and Inotropesmentioning
confidence: 99%
“…Conversely, it can be shown that the contractility changes caused by acidosis are offset by increased catecholamine production. This concept was supported by the observation in rabbits that although hypercapnic acidosis caused a decrease in contractility, thoracolumbar epidural anesthesia increased this depression considerably by blocking sympathetic activity [31].…”
Section: Metabolic Acidosis Organ Dysfunction and Outcomes Of Septicmentioning
confidence: 95%